Rethinking Mother Tongue Instruction After RA 12027: An Ilokano-Based Translanguaging Approach for Multilingual K–3 Learners - Leonardo Tejano (Educalingua Journal, 2026)
Republic Act No. 12027, enacted on October 10, 2024, discontinued the mandatory implementation of Mother Tongue-Based Multilingual Education (MTB-MLE) in Philippine public schools, relegating regional languages to the status of ‘auxiliary media’ beginning School Year 2025–2026. Yet this legislative shift does not alter the multilingual realities of Ilokano-speaking children in the Ilocos Region. Grounded in translanguaging theory and utilizing a descriptive survey design with thematic analysis, this study examined the language backgrounds, translanguaging practices, and functional languaging roles of K–3 learners across selected schools in Ilocos Norte, involving 136 surveyed learners, 73 individual interviews, 43 teachers, and 18 parents across eight focus group discussions. Five characteristics of learner translanguaging and four distinct roles of Ilokano were identified: (1) fluidity of language use, (2) Ilokano dominance in informal interaction, (3) metalinguistic awareness, (4) translanguaging for cognitive scaffolding, and (5) identity-bound language loyalty. Four distinct roles of Ilokano were likewise established: Ilokano as (1) main language of expression, (2) consolidator of linguistic features, (3) metalinguistic comparator, and (4) organizer of ideas, with particular pedagogical significance residing in its role as a cognitive scaffold that bridges L1-based meaning-making with formal L2 academic output. Drawing on these empirical findings, the study proposes the Ilokano-Based Translanguaging Approach (IBTA)—a theoretically grounded, multi-stranded pedagogical framework that mobilizes learners’ full multilingual repertoire while positioning Ilokano as both instructional anchor and object of language revitalization. The IBTA is structured around teacher preparation, instructional materials development, and teaching strategy, offering a statutory-compliant, evidence-based model for embedding Ilokano-based multilingual pedagogy within the MATATAG Curriculum under the post-RA 12027 policy environment.